2014
DOI: 10.1212/cpj.0000000000000081
|View full text |Cite
|
Sign up to set email alerts
|

Cost-saving innovations for acute ischemic stroke and transient ischemic attack

Abstract: SummaryHealth care costs continue to rise toward unsustainable levels that will affect our nation's ability to support other key funding priorities for education, military, and infrastructure. Changing the way we deliver health care is critical to mitigating this financial crisis. This review highlights opportunities for redesigning care of acute ischemic stroke and TIA to maintain quality while substantially lowering costs. The recent innovations described are (1) adopting teleneurology networks to improve ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Additionally, mitigating delays and preventing reluctance to seek medical care requires addressing various factors such as overcoming fear of COVID-19 infection 115 ; managing transportation restrictions (i.e., many individuals indicated being ensure whether travel to hospital was permitted and feared exposing patients to COVID-19 116 ), and alleviating burdens on the healthcare system. Notably, innovations have been proposed to alleviate these burdens and safeguard stroke survivors during crises, including: (1) implementing teleneurology networks to enhance thrombolysis access for acute ischemic stroke; (2) enhancing the efficiency of emergency care for acute ischemic stroke (e.g., by preregistering patients during transport via ambulance and having the neurologist obtain clinical history electronically prior to arrival at the hospital); and (3) offering alternatives to inpatient care for transient ischemic attacks through an accelerated diagnostic protocol in the observation unit 117 . This emphasizes the importance of rapid adaptation and multidisciplinary changes in stroke care protocols, including effective triage screening, proper PPE utilization, and increased equipment cleaning to minimize treatment delays 118 .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, mitigating delays and preventing reluctance to seek medical care requires addressing various factors such as overcoming fear of COVID-19 infection 115 ; managing transportation restrictions (i.e., many individuals indicated being ensure whether travel to hospital was permitted and feared exposing patients to COVID-19 116 ), and alleviating burdens on the healthcare system. Notably, innovations have been proposed to alleviate these burdens and safeguard stroke survivors during crises, including: (1) implementing teleneurology networks to enhance thrombolysis access for acute ischemic stroke; (2) enhancing the efficiency of emergency care for acute ischemic stroke (e.g., by preregistering patients during transport via ambulance and having the neurologist obtain clinical history electronically prior to arrival at the hospital); and (3) offering alternatives to inpatient care for transient ischemic attacks through an accelerated diagnostic protocol in the observation unit 117 . This emphasizes the importance of rapid adaptation and multidisciplinary changes in stroke care protocols, including effective triage screening, proper PPE utilization, and increased equipment cleaning to minimize treatment delays 118 .…”
Section: Discussionmentioning
confidence: 99%
“…Identifying these factors and understanding their impact on cost can help healthcare providers to optimize treatment and minimize costs without compromising patient outcomes. Several strategies can be adopted to minimize costs, in particular, the adoption of teleneurology networks to improve access to thrombolysis for acute ischemic stroke, improving efficiency of emergency care for acute ischemic stroke, and provide alternatives to hospital care [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study done in the USA tele-stroke has demonstrated cost-saving benefits by enabling the treatment of a greater number of patients with IV tPA and increasing the number of discharges straight to the patient’s home, hence minimizing the need for long-term rehabilitation stays and saving up to $44,000 yearly per hospital in the network. However, since existing compensation for telemedicine is restricted by law to specific specialities and low-access locations, cost-sharing programs or assistance from the state and federal levels are required to make telemedicine networks commercially viable 25 .…”
Section: The Process Of Tele-stroke Carementioning
confidence: 99%